Education-occupation mismatch in the context of informality and development - Aleksynska, Mariya (OECD Development Centre Working Papers, 2021)
Using household data from 15 countries in Latin America and Africa, this paper explores linkages between informality and education-occupation matching. The paper applies a unified methodology to measuring education-occupation mismatches and informality, consistently with the international labour and statistical standards in this area. The results suggest that in the majority of low- and middle-income developing countries with available data, workers in informal jobs have higher odds of being undereducated as compared to workers in formal jobs. Workers in formal jobs, in contrast, have higher chances of being overeducated. These results are consistent for dependent as well as for independent workers. They also hold for men and for women according to the gender-disaggregated analysis. Moreover, in the majority of countries considered in this paper, the matching-informality nexus is also related to the extent of informality in a given area: in labour markets with higher informality, informal workers in particular have a higher chance of being undereducated. The paper discusses policy implications of these findings